Relationship of subjective well-being with social support and meaning in life among college students - Nellissery, Aji Antony (Sherin Maria) (Animo Repository, 2005)
This study sought to determine the relationship and predictive influence of social support and meaning in life on the components of subjective well-being (life satisfaction, positive affect and negative affects) among the first year college students. The participants were 141 (81females and 60 males) first year college students from Metro Manila. The data collected from four standardized instruments, namely: Student Life Satisfaction Scale (SLSS) of Huebner, (1991) Positive and Negative Affective Schedule (PANAS) of Watson, Clark, & Tellegen, (1988) Social Support Appraisal Scale (SSA) of Vaux, Phillips, Holley, Thompson, Williams, and Stewart (1986) and Purpose in Life Test (PIL) of Crumbaugh and Maholick (1969) were used to measure the components of subjective well-being of the respondents. Correlational design and multiple regression analysis were employed in this study. The findings of the study show that there was a significant correlation between social support and the components of subjective well-being (life satisfaction and positive affect) and also between meaning in life and the components of subjective well-being (life satisfaction and positive affect). Social support and meaning in life were not significantly correlated and predicted with the negative affective component of subjective well-being. The results of multiple regression analysis showed that social support and meaning in life were predictive of subjective well-being (life satisfaction, positive affect). The research findings further revealed that in the life of first year college students, both interpersonal variable (social support) and intrapersonal variable (meaning in life) have influence on subjective well-being (life satisfaction and positive affect).